POLICY OF SELF-DEVELOPMENT OF RECIPIENT REGIONS - Semyon Egorov; Igor Kuznetsov (Вестник Северо-Кавказского федерального университета)
In modern russian conditions the special relevance is acquired by a problem of high differentiation ofregions on the level ofsocial and economic development and difference in degree of economic dependence of regions on the federal center. For an exit from current situation in article the possibilities of realization by recipient regions of policy of self-development are considered. The concept «self-development» is for this purpose opened, the reasons of lag of regions on the level of social and economic development are established, the general signs of underdeveloped recipient regions are marked out. It is defined that effective instruments of ensuring transformation of recipient regions in spontaneous have to be created in the course of modernization of regional policy.